Complete the operation. (-a - 6b + 4)3ab


Complete the operation.

(-a - 6b + 4)3ab

Expanding Terms

Performing the required operation means we have to expand the expression given. This involved opening the brackets. Opening the brackets when there is a term outside requires the use of the distributive law. This is:

$$x(y+z)=xy+xz $$

Answer and Explanation:

The operation is completed as follows.

$$\begin{align} & (-a - 6b + 4)3ab\\ =&-3ab*a-3ab*6b+3ab*4&&&&\left [ \because x(y+z)=xy+xz,x(y-z)=xy-xz \right ]\\ =&-3a^{1+1}b-18ab^{1+1}+12ab&&&&\left [ \because axy*x=ax^{1+1}y \right ]\\ =&-3a^2b-18ab^2+12ab \end{align} $$

Learn more about this topic:

What is Expanded Form in Math? - Definition & Examples

from CBEST Test Prep: Practice & Study Guide

Chapter 12 / Lesson 9

Related to this Question

Explore our homework questions and answers library